Foreign listings in Singapore Stock Exchange (SGX). - Cheng, Ze Ying. (2008)
This study is on foreign listings in SGX based on three prospects. Firstly, this study examines pre and post listing performance of foreign firms that list on the SGX to realize the benefits of listing oversee. The result suggests that foreign firms although experience an increase in stock return after one year of listing, this is not the case for operating performance. Secondly, this study seeks to analyze the financial performance difference between foreign and local firms that list on SGX and result shows that foreign firms do have a better quality in terms of returns and profit earned prior to listing but experience similar performance after listing. Finally, this study analyzes the differences in performance between sector and outcome suggests that the impact of sector differences only affect firms’ stock performances and barely affecting their operating performance. Conclusions are drawn that foreign firms listing in the SGX generally perform as well as local firms in terms of stock returns and operating performance are also similar to local firms after one year of listing.